Production of Radioisotopes and Radiopharmaceuticals at the Dalat Nuclear Research Reactor - Duong , Van Dong; Pham , Ngoc Dien; Bui , Van Cuong; Mai , Phuoc Tho; Nguyen , Thi Thu; Vo Thi , Cam Hoa (Nuclear Science and Technology, 2014)
After reconstruction, the Dalat Nuclear Research Reactor (DNRR) was inaugurated on March 20th, 1984 with the nominal power of 500 kW. Since then the production of radioisotopes and labelled compounds for medical use was started. Up to now, DNRR is still the unique one in Vietnam. The reactor has been operated safely and effectively with the total of about 37,800 hrs (approximately 1,300 hours per year). More than 90% of its operation time and over 80% of its irradiation capacity have been exploited for research and production of radioisotopes. This paper gives an outline of the radioisotope production programme using the DNRR. The production laboratory and facilities including the nuclear reactor with its irradiation positions and characteristics, hot cells, production lines and equipment for the production of Kits for labelling with 99mTc and for quality control, as well as the production rate are mentioned. The methods used for production of 131I, 99mTc, 51Cr, 32P, etc. and the procedures for preparation of radiopharmaceuticals are described briefly. Status of utilization of domestic radioisotopes and radiopharmaceuticals in Vietnam is also reported.